A Case Report The Evaluation of Malondialdehyde Level on Acne Vulgaris Treatment - Muhammad Ridlo; Nelva K. Jusuf (Talenta Publisher, 2022)
Abstract: Acne vulgaris (AV) is a multifactorial disease of the pilosebaceous unit with varying degrees of severity, recurrent and characterized by polymorphic lesions. Recent studies have found that the etiopathogenesis of AV is caused by oxidative stress. Each factor that causes AV is interrelated and is under the control of hormones and immunity. Measurement of malondialdehyde (MDA) level in the blood becomes a biological marker or an indicator of cell and tissue damage caused by oxidative stress. Case: A 23-years-old female private employee visited the clinic for multiple comedones and papulopustular lesions scattered over cheeks, nose, and chin that spread to the whole face four months ago. There were multiple comedones, papules, pustules, nodules on the maxillary, nasalis, left and right zigomatic, mentalis and frontalis region. We also found multiple scars on the left and right buccal. She was diagnosed with Severe AV. Serum MDA level was measured according to the enzyme-linked immunosorbent assay (ELISA) method before and after therapy. She was treated with doxycycline 100 mg, 0.025% tretinoin cream, 5% benzoyl peroxide, 1.2% clindamycin gel, and broadspectrum sunscreen with SPF 50. Result: After eight weeks of treatment, there were noticeable improvements in acne lesions and overall healthier-looking skin. Serum MDA levels are decreased (22.6 nmol/ml to 17.9 nmol/ml) as the impact of the therapy. Keyword: Acne Vulgaris, Malondialdehyde, Oxidative Stress